2019
DOI: 10.1002/app.47975
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and diffusivity of carbon‐reinforced polyetherketoneketone composites

Abstract: Heat transfer properties play an important role in processing of polyetherketoneketone (PEKK)/carbon fiber (CF) composites. Accordingly, thermal conductivity and diffusivity of PEKK, PEKK/glassy carbon (GC), and PEKK/CF composites have been studied. Observed increase in conductivity and diffusivity with carbon filler addition was analyzed using the Maxwell-Eucken model. PEKK/GC composites with low carbon fraction indicated good fitting experimental points of the model, indicating good dispersion of particles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…All foams showed a reduced thermal conductivity by 40–53% compared to the bulk PMMA (Figure 8A), yet only the neat foam and the foam with clusters and aggregates reasonably matched with the Maxwell–Eucken model for closed‐cell porosity foams. [ 40 ] On the contrary, the thermal conductivity of the dispersed NPs exceeded the theoretical prediction by 20.6% (Figure 8A). The void size reduction, brought about by the NPs, favors lowered thermal conductivity, although the voids remain too large to experience Knudsen's effect.…”
Section: Resultsmentioning
confidence: 75%
“…All foams showed a reduced thermal conductivity by 40–53% compared to the bulk PMMA (Figure 8A), yet only the neat foam and the foam with clusters and aggregates reasonably matched with the Maxwell–Eucken model for closed‐cell porosity foams. [ 40 ] On the contrary, the thermal conductivity of the dispersed NPs exceeded the theoretical prediction by 20.6% (Figure 8A). The void size reduction, brought about by the NPs, favors lowered thermal conductivity, although the voids remain too large to experience Knudsen's effect.…”
Section: Resultsmentioning
confidence: 75%
“…As mentioned in other works in the literature, the diffusion is thermally activated and follows an Arrhenius type law. The characterization of the moisture diffusion kinetics at high temperatures has shown that the diffusion coefficients even at high temperatures are very low and largely lower than the thermal diffusivity (between 10 −6 and 10 −7 m 2 •s −1 [69]). Moisture diffusion is thus slower than heat diffusion in CF/PEKK.…”
Section: Moisture Transport Kinetics Inmentioning
confidence: 99%
“…(The original simulation in [10] also considered the thermal contact resistance.) Hence, = 0.25 W/m/K from [43] was adopted for PEKK in all further simulations. The subsequent Sim.5-1 delivered a better prediction than Sim.5-0, with slower cooling rates and a reheating peak of lower height but larger width.…”
Section: Set 5 and The Uncertainty In The Emissivitymentioning
confidence: 99%